The international repercussions of EC agricultural policy - Peter Michael Schmitz (Intereconomics, 1985)
The importance of the EC in international agricultural markets has grown steadily since the establishment of the Community and will receive another boost following its southward enlargement. Nevertheless, agricultural policy has been inward-looking and has paid, little heed to the external effects it engenders. Prof. Schmitz shows that EC agricultural policy has tended to depress world market prices, has increased their volatility and artificially distorted the price structure in the world market.
Keywords: 330; Agricultural Policy